Potential of Waste Toner Powder for Sustainable Energy Production: An Assessment of Its Suitability for Bio-Briquette Applications - Taşar, Şeyda; Yılgın, Melek; Duranay, Neslihan; Pehlıvan, Dursun (My University, 2025)
This study investigates the feasibility of utilizing waste toner powder (WTP) in the energy sector, focusing on its application in bio-briquette production. The research comprised two main phases: the characterization of WTP’s structural, morphological, and fuel properties, followed by an evaluation of its potential as a biofuel component in direct combustion processes. WTP samples were collected from a recycling facility specifically established for toner cartridge recycling in the Elazığ Organized Industrial Zone. These samples were stored under appropriate conditions and analyzed using advanced techniques. The structural and morphological properties were examined using FTIR, SEM-EDX, and particle size distribution analyses. Particle size measurements revealed average diameters of 182.6 nm in toluene and 308.4 nm in benzene, with toluene providing a narrower and more uniform distribution. Fuel properties were assessed through proximate and ultimate analyses. The results indicated that WTP contains 88.38% volatile matter, 4.91% ash, and 2.67% moisture, with a higher heating value (HHV) of 35.56 MJ/kg. The ultimate analysis highlighted a significant carbon content (32.12%) and low nitrogen levels (1.98%), reinforcing its potential as a fuel. WTP’s dispersion behavior was also evaluated in both media, confirming better stability in toluene. These findings demonstrate that WTP possesses favorable fuel properties, such as a high calorific value and strong binding capabilities, making it a promising raw material for bio-briquette production when mixed with powdered biomass waste sources like furniture factory waste. Producing biofuel pellets with WTP could enhance energy efficiency, reduce emissions, and improve transport and storage convenience. Utilizing WTP as an energy source not only provides a high-value solution for waste management but also supports environmental sustainability and landfill preservation.
Keywords: Energy Recovery; Waste Toner Powder; Bio-briquette; E-Waste Recycling; Sustainable Fuel Development